Fintech Usage, Risk Perception, and Data Privacy Concerns on Trust in Digital Financial Services in Indonesia - Wahyuni Sri Astutik; Adih Supriadi (Westscience Press, 2026)
This study aims to analyze the effect of fintech usage, risk perceptions, and data privacy concerns on trust in digital financial services in Indonesia. The rapid development of financial technology has increased the adoption of digital financial services; however, trust remains a crucial factor influencing user acceptance and continued usage. This research employs a quantitative approach using primary data collected from 150 respondents through structured questionnaires measured on a Likert scale. Data analysis was conducted using SPSS version 25, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that fintech usage has a positive and significant effect on trust, indicating that higher levels of usage and familiarity increase user confidence in digital financial services. Conversely, risk perception has a negative and significant effect on trust, suggesting that concerns about financial loss, system errors, and fraud reduce users’ willingness to rely on fintech platforms. Similarly, data privacy concerns are found to negatively and significantly influence trust, highlighting that fears related to personal data misuse and security breaches undermine user confidence. Simultaneously, fintech usage, risk perception, and data privacy concerns significantly affect trust, with an R² value of 0.465, indicating that 46.5% of the variation in trust is explained by these variables. This study contributes to the literature by providing empirical evidence on the determinants of trust in digital financial services in Indonesia. The findings offer practical implications for fintech providers and policymakers to enhance user trust by improving system security, strengthening data protection measures, and increasing user awareness of fintech services.